Religious processes on the territory of Mongolia (Based on the results of sociological research) - Petr Konstantinovich, Dashkovskiy; Magsarjav, Gantuya; Elena Alexandrovna, Shershneva (Studia Philosophiae Et Juris, 2022)
The article presents the results of a sociological study conducted by the Russian-Mongolian project in 2020 on the territory of Mongolia. In the course of the study, an attempt was made to assess the religious situation on the territory of Mongolia and to identify the degree of involvement of the country's residents in religious life, as well as their perception of state confessional policy. The sample of the study is 362 people. At the same time, the number of respondents included a significant number of respondents who came to Ulan-Bator to study or work from different parts of the country. However, 46% of respondents visit places of worship very rarely, and 22% do not observe any religious rites at all. This fact indicates a rather weak involvement of respondents in religious life, including the Buddhist sangha. Research has shown that Buddhism is the predominant denomination in Mongolia, which is considered as part of the national culture of the Mongolian people. The State is taking measures to support the Buddhist institute as an element of national identity. These measures lead to the popularization of Buddhism among the population of Mongolia. According to respondents, an important role in building interfaith dialogue should be played by the state, whose task is to control the activities of religious organizations. It is established that stereotypes associated with religious traditions prevail in Mongolian society. Thus, the majority of respondents associate Islam with manifestations of extremism. At the same time, it should be noted that Mongolia is a country with a fairly low level of extremist worldview. The assessment of the development of the interfaith situation in Mongolia requires further observation. Монгол Улсын нутаг дэвсгэр дээрх шашны үйл явц (социологийн судалгааны үр дүнгээр) Энэхүү өгүүлэлд Орос-Монголын хамтарсан төслөөс 2020-2021 онд Монгол Улсын нутаг дэвсгэрт хийсэн социологийн судалгааны үр дүнг танилцуулж байна. Судалгааны явцад Монгол Улсын нутаг дэвсгэр дэх шашны нөхцөл байдалд үнэлэлт дүгнэлт өгөх, тус улсын иргэд шашны үйл ажиллагаанд хэрхэн оролцож байгаа болон төрөөс явуулж буй шашны бодлого ямар байгааг тодорхойлох оролдлого хийсэн. Судалгаанд 362 хүн хамрагдав. Үүний зэрэгцээ судалгаанд Монгол Улсын өнцөг булан бүрээс Улаанбаатар хотод суралцах, ажиллахаар ирсэн хүмүүсийг түүвэрлэн багтаасан болно. Буддын шашин бол Монголын ард түмний үндэсний соёлын нэг хэсэг, монголчуудын шүтдэг зонхилох шашин гэдгийг судлаачид тогтоодог. Буддын шашны сүм хийдийг үндэсний өвөрмөц соёлын нэг хэсэг болгон дэмжих арга хэмжээг төрөөс авч хэрэгжүүлдэг. Эдгээр арга хэмжээ нь Монгол дахь Буддын шашны зонхилох байр суурийг хадгалахад чиглэж байгаа юм. Судалгаанд оролцогчдын үзэж байгаагаар шашин хоорондын харилцан ойлголцлыг бий болгох үүднээс шашны байгууллагуудын үйл ажиллагаанд хяналт тавих нь төрийн чухал үүрэг байх ёстой. Монголын нийгэмд шашны уламжлалтай холбоотой хэвшмэл ойлголт давамгайлж байгаа нь тодорхой байна. Тиймээс судалгаанд оролцогчдын дийлэнх нь шашны туйлшралын илрэлийг гол төлөв Исламын шашинтай холбож үзжээ. Нөгөө талаар, Монгол Улсад ертөнцийг үзэх хэт туйлширсан өрөөсгөл үзэл харьцангуй бага гэдгийг тэмдэглэн хэлэх хэрэгтэй. Гэхдээ Монгол дахь шашин хоорондын харилцааны нөхцөл байдлын өрнөлийг үнэлэхэд цаашид ажиглалт судалгаа хийх шаардлагатай байгаа юм. Tүлхүүр үгс: соёлын амьдрал, буддын шашин, шашны уламжлал, шашны туйлшрал, үндэсний соёл